INNOVATIVE TRANSFORMATION OF THE NATIONAL ECONOMY: REGIONAL, GLOBAL AND INSTITUTIONAL ASPECTS (INNOVATIVE ECONOMY, 2024)
Savluk R.Ya., Viertseva A.O.  INNOVATIVE TRANSFORMATION OF THE NATIONAL ECONOMY: REGIONAL, GLOBAL AND INSTITUTIONAL ASPECTSPurpose. The aim of the article is to generalize the current trends in the development of the national economy, determine the influencing factors on its dynamics and substantiate the tools of institutional influence on innovative modernization.Methodology of research. The theoretical and methodological basis of this research is a systematic approach to the definition and generalization of global, regional, institutional and structural factors of influence on the current state and trends of the development of the national economy; structural and functional analysis of macroeconomic trends in the development of national production; an institutional-evolutionary approach to substantiating the toolset for regulation of innovative development and activation of the innovation process in the economy.Findings. It is emphasized that the minimizing the negative effects of global dynamics, cyclical, social and political risks can be achieved by the high dynamics of economic growth, which is determined by the state and interaction of the basic factors of reproduction, which are appropriate and adaptive to the level of technological progress achieved by the country.A low share of the export of high-tech goods from the national economy was established, which is due to the low innovative activity of domestic manufacturers, the lack of prerequisites for the innovative development of the economy, the lack of funding and the low share of R&D spending.It is argued that ensuring a higher level of technological efficiency of domestic production requires the support and development of Ukrainian science and improvement of the model of the organization of the innovation process; implementation of financial programs to support the innovative development of industries and regions.Originality. The need to achieve a harmonious combination of the driving forces of modernization (state, market, society) in the implementation of the strategic direction of the development of the social and economic model is substantiated.It is argued that the negative effects of globalization, regional, economic, social and political problems can be resisted by innovative transformation, which accelerates economic dynamics; contributes to the growth of production productivity, volumes of international trade; adaptability of the economic system to conditions of high risks and adverse exogenous changes.In view of the strategic priority of implementing innovative modernization in the national economy, the institutional role of the state should be implemented by including in formal norms and existing institutions incentives for the innovative activity of domestic product manufacturers, as well as by forming an institutional environment that will activate innovative transformations.Practical value. The theoretical and methodological provisions of the study deepen the practical aspects and tools of institutional regulation of innovative modernization of the national economy and can serve as a basis for further scientific research.Key words: innovative transformation, innovative dynamics, innovative development, globalization, regionalization, industry structure, national economy, integration, institute, institutional regulation, institutional support.
Keywords: innovative transformation; innovative dynamics; innovative development; globalization; regionalization; industry structure; national economy; integration; institute; institutional regulation; institutional support.